Effect of post-resettlement support policies for Ningxia reservoirs - Wang, Le; Lu, Yang; Li, Taiyun (Frontiers in Sustainable Cities, 2025)
With the economy’s and society’s rapid development, reservoir construction has gradually become an essential infrastructure for water resource regulation, flood control and disaster reduction, and power generation. However, involuntary migration is an increasingly prominent global challenge, presenting a common challenge worldwide. Ningxia Hui Autonomous Region is located in the northwest of China, in the upper and middle reaches of the Yellow River basin, and is a typical arid and rainless area. To improve the uneven spatial and temporal distribution of water resources and ensure regional economic and social development, Ningxia actively promotes the construction of water conservancy infrastructure such as reservoirs. However, the large-scale immigration problem brought about by reservoir construction has also become an important social challenge that the region has long faced, attracting widespread attention from all walks of life. To enhance the lives of emigrants in the reservoir areas, the Ningxia Hui Autonomous Region government has implemented a series of post-resettlement support policies since 2006. This paper constructs an evaluation index system specifically for these post-resettlement support policies for Ningxia reservoirs, calculating a comprehensive index. A panel regression model is employed to empirically analyze the result of post-resettlement support policies on GDP, industrial development, residents’ income, and government budget deficits. Our research finds that post-resettlement support policies for Ningxia reservoirs can significantly promote local economic development and alleviate fiscal deficit rates but demonstrate an inhibitory effect on both industrial development and household income growth. Further analysis indicates that the result of post-resettlement support policies on residents’ income and the level of industrial development exhibits a U-shaped relationship, namely a nonlinear relationship of declining first and then rising. This paper not only enriches the theoretical framework of post-resettlement support policies for the reservoirs but also gives empirical evidence for policymakers to assist in poverty alleviation and wealth creation for emigrants in reservoir areas, promote economic and social development in reservoir and immigrant areas, and build a harmonious society.